IMPLEMENTASI PENATAAN REGULASI PENANAMAN MODAL DALAM HUKUM INVESTASI DI INDONESIA MELALUI UNDANG-UNDANG NOMOR 11 TAHUN 2020 TETANG CIPTA KERJA - ade muhamad putra; hamzah hamzah (MIH Unsoed, 2022)
After the issuance of Law Number 25 of 2007 concerning Investment, foreign and domestic investors were given equal treatment. Equal treatment of domestic and foreign capital is an important principle of investment policy. Article 6 paragraph (1) of Law Number 25 of 2007 states that the Government provides equal treatment to all investors originating from any country conducting investment activities in Indonesia in accordance with the provisions of the legislation. Furthermore, paragraph (2) states that such treatment does not apply to investors from a country that obtains special rights based on an agreement with Indonesia. Law No. 11 of 2020 concerning Job Creation is expected to be able to absorb the widest possible Indonesian workforce in the midst of increasingly competitive competition and the demands of economic globalization. With the ease and simplification of the entry of foreign investment and foreign workers in Indonesia, it is able to attract the interest and desire of foreign investors to invest in Indonesia.